Analysis The Use of Audio-Visual Learning Media to Increase Students' Learning Interest at 4th Class IPAS Subjects SDN 1 Sigar Penjalin - Putra, Iwan Wahyudi; Arzani, M.; Muhajirin, Muhammad (Peneliti.net, 2025)
This study aims to, (1) analyse the use of audio-visual learning media in increasing students' interest in learning in class IV Natural and Social Sciences (IPAS) subjects at SDN 1 Sigar Penjalin, (2) describe the supporting and inhibiting factors for teachers in using audio-visual media in class IV SDN 1 Sigar Penjalin, and (3) describe the impact of using audio-visual media in increasing students' interest in learning in IPAS subjects in class IV SDN 1 Sigar Penjalin. This research uses a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects were IPAS subject teachers, principals, and grade IV students of SDN 1 Sigar Penjalin. Data were analysed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the use of audio-visual media in IPAS learning was able to increase students' attention, involvement, and enjoyment of the learning process. Supporting factors found include teacher readiness, availability of facilities, and school support. Meanwhile, inhibiting factors include limited technological devices and lack of training for teachers. The positive impacts of using this media include increased student interest in learning, a more lively classroom atmosphere, and better student understanding of the material.